Intelligent collaborative agent for jobs match - Mat Cha, Md Zahir; Dahari@Damiri, Rohaya
This research report detailed out the study and development of Electronic Job Matching Agent namely, JobsMatch.The idea of JobsMatch came into light when Practical Training Unit and students encounter difficulties while trying to look for practicum placement.JobsMatch also design and develop to aid employer and at the same time to provide job seekers with an attractive and friendly environment for posting ads and finding jobs.The Internet provides the medium for conducting the recruitment and selection process in an online environment.JobsMatch was constructed with an agent that automatically generate resumes/curriculum vitae, serve of posting job ads, matching resume with job ads and listing selected candidates to be review by employer.More specifically, in order to meet hiring objectives and control the increasing cost of recruiting, the conclusions of this project suggest that organizations should implement an online recruiting and selection process.The critical requirements of the JobsMatch model are: eliminating paperwork, improving time-to-hire, reducing turnover, creating a resume and position-centric environment as well as using Internet as a recruitment and selection tool.